Study to Evaluate the Factors Affecting Delayed Discharge/Transfer of Patients from the Emergency Room and Its Impact on Patient Volume. - Dahiya, Vikas (Digital Repository of Theses, 2025)
A study is being conducted to evaluate the various elements affecting the delayed discharges/transfers of patients from the emergency room to either ward or home, as well as their effect on patient turnover in the emergency room. Increased patient wait time in the emergency room of a hospital is a worldwide challenge. Staying in the emergency room for more than 12-15 hours increases mortality and morbidity rates, health care costs, and patient satisfaction. The emergency department becomes overcrowded, which leads to prolonged patient stays, which in turn is associated with several problems in patient care. Aim—The aim is to find out the reasons for delays and stay of patient and time to wait getting treatment in the emergency room in the department, treatment, and discharge of the inpatient to home or ward/ICU. The goal of the study is to create a strategy that is going to resolve the factors of area delay in the emergency department. So as to decrease the cost, improve patient satisfaction, and quick decision making for the doctors.